ELIMINASI HARMONISA PADA INDUCTION FURNACE MENGGUNAKAN FILTER HYBRID - Hadi Setiawan; Belly Yan Dewantara; Istiyo Winarno (Universitas Muhammadiyah Gresik, 2024)
Induction Furnace is equipment that is widely used in the metal or steel industry, this equipment is usually used to process metallic or non-metallic minerals in the reduction or smelting process. Induction furnaces have a frequency value in an induction furnace that can reach 2000Hz, and the DC voltage can be adjusted to reach 800VDC. By using a filter you can reduce harmonics as small as possible until the waveform is closer to sinusoidal. Research to analyze the steps for installing a hybrid filter to reduce harmonic distortion. The analysis results from the hybrid filter simulation can reduce the total harmonic distortion value with the THD value according to IEEE 152-1992.